Workshop Project Penguatan Profil Pelajar Pancasila Untuk Menanamkan Karakter pada Anak PAUD melalui Kegiatan Kemerdekaan - Nurul Ilmi Azizah, Annafi; Wardani, Anita; Intan Apriliani, Elina; Widayanti, Wahyu (Seulanga: Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this activity is to provide examples of various activities that can be implemented in each PAUD institution, namely Independence activities that contain many benefits, especially in instilling character in children. Characters that can be developed such as the character of love for the country, patriotism, brave, responsible, honest, willing to sacrifice, helpful, respect for differences, etc. The methods used in this training activity are preparation, implementation, and evaluation. The preparation method includes meeting with 35 teachers at RA Chairunnisa to coordinate activities. The implementation method includes material presentation on the preparation of P5 independence activities from the beginning stage, development stage and conclusion stage. In addition, the practice of making Independence activities by making a variety of Indonesian traditional costumes, making war equipment such as guns, swords, rifles and simulating independence competitions. The evaluation method is in the form of discussions and questions and answers between participants and resource persons. The result is that teachers understand how the steps in the preparation of project activities to strengthen the profile of Pancasila students (P5), teachers have ideas and ideas for preparing interesting activities on Independence Day that contain many benefits, especially in instilling children's character.